ANALISIS FAKTOR KEBERLANJUTAN BANK SAMPAH KOTA MADIUN (Studi Kasus pada Bank Sampah Matahari Madiun) - Windyaningrum, Theresia Liris (Widya Warta, 2021)
This study aimed to examine the factors that influenced the potential sustainability of a waste bank in Madiun, especially at the Bank Sampah Matahari Madiun through the role of the waste bank management. The research sample was management personnel of the Bank Sampah Matahari Madiun using saturated sampling. Methods of data analysis used regression analysis and hypothesis testing. The results of the analysis showed that the role of the management in planning and implementation of environmental empowerment had a significant impact simultaneously on the sustainability of the waste bank in Bank Sampah Matahari Madiun by 78,8%.